Current and historical individual data about exposure of workers in the rayon industry to carbon disulfide and their validity in calculating the cumulative dose - Göen, Thomas; Schramm, Axel; Baumeister, Thomas; Uter, Wolfgang; Drexler, Hans (International Archives of Occupational and Environmental Health, 2014)
The objective of the study was to investigate how exposure to carbon disulfide (CS2) in a rayon-manufacturing plant has changed within two decades and whether it is possible to calculate valid data for the individual cumulative exposure.The data for CS2 concentration in air and biological exposure monitoring (2-thio-1,3-thiaxolidine-4-carboxylic acid (TTCA) in urine) from two cross-sectional studies, performed in 1992 (n = 362) and 2009 (n = 212) in a German rayon-manufacturing plant, were compared to data obtained from company-internal measurements between the studies.Using the data from the cross-sectional studies and company-internal data, cumulative external exposure and the cumulative internal exposure were calculated for each worker. External and internal CS2 exposure of the employees decreased from 1992 (medians 4.0 ppm and 1.63 mgTTCA/g creatinine) to 2009 (medians 2.5 ppm and 0.86 mg/g). However, company-internal CS2 data do not show a straight trend for this period. The annual medians of the company-internal measurement of external exposure to CS2 have varied between 2.7 and 8.4 ppm, in which median values exceeded 5 ppm generally since 2000. The annual medians for the company-internal biomonitoring assessment ranged between 1.2 and 2.8 mg/g creatinine. The cumulative CS2 exposure ranged from 8.5 to 869.5 ppm years for external exposure and between 1.30 and 176.2 mg/g creatinine years for the internal exposure. Significant correlations were found between the current air pollution and the internal exposure in 2009 but also between the cumulative external and internal CS2 exposure.Current exposure data, usually collected in cross-sectional studies, rarely allow a reliable statement on the cumulative dose, because of higher exposure in the past and of fluctuating courses of exposure. On the other hand, company-internal exposure data may be affected by non-representative measurement strategies. Some verification of the reliability of cumulative exposure data may be possible by testing the correlation between cumulative exposure data of external assessment and biological monitoring.
EVALuna2:5395

Increased intima-media thickness in rayon workers after long-term exposure to carbon disulfide - Schramm, Axel; Uter, Wolfgang; Brandt, Meike; Göen, Thomas; Köhrmann, Martin; Baumeister, Thomas; Drexler, Hans (International Archives of Occupational and Environmental Health, 2016)
Long-term exposure to carbon disulfide (CS2) is associated with increased cardiovascular mortality. However, previous studies on actual vascular changes showed heterogeneous results. Intima-media thickness of the carotid arteries (IMT) represents an established marker of atherosclerosis and a reasonable surrogate marker for cardiovascular risk. IMT was examined in a large cohort of CS2 exposed workers and the association with cumulative CS2 exposure analysed.In a cross-sectional examination, 290 exposed and 137 non-exposed workers in a German rayon-manufacturing plant were assessed. Individual cumulative exposure was calculated from this assessment combined with the results of two cross-sectional studies in 1992 and 1999 and department-specific annual means of ambient (CECS2) and individual biological (CETTCA) monitoring results obtained 1992-2009. Furthermore, cumulative duration of working in CS2-exposed departments (CEYEARS) was calculated. Examination included assessment of a broad set of known cardiovascular risk factors and IMT measurement of the carotid arteries on both sides. Multiple linear regression analyses were performed with IMT as outcome and three variants of cumulative exposure (duration of exposure, cumulative CS2, and cumulative TTCA) as well as categorised maximum CS2 exposure, all adjusted for cardiovascular risk factors.All models of cumulative exposure showed a significant increase in IMT in the group with the highest level of exposure: CEYEARS > 20 years, ? = 0.045 mm; CECS2 > 270 ppm × years, ? = 0.052 mm; CETTCA > 33 mg/g creatinine × years, ? = 0.038 mm. Alternatively, addressing maximum exposure, workers with CS2 exposure of >10 ppm in at least 3 years exhibited a significant IMT increase (? = 0.068 mm).Long-term CS2 exposure is an independent risk factor concerning IMT changes. The amount of IMT increase, in a similar range as that associated with other cardiovascular risk factors, might be clinically relevant.
EVALuna2:5493